2016
DOI: 10.1504/ijscim.2016.076407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of information sharing on the performance of a four stage serial supply chain under back order and lost sale situations

Abstract: In any supply chain (SC) system, information sharing is very important as it supports other SC drivers to enhance coordination and it thereby improves the performance of the entire SC. The objective of this study is to analyse the performance of a four level serial SC under eight different kinds of information sharing cases, with backorder and lost sales situations. The study has been done using experiments on SC simulation game software called 'SC role play game'. Steady state results from the game under diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Further, they examined the effects of serially correlated demands on probabilistic lost-sale inventory model. Further, Ambilikumar et al (2016) have analysed the performance of a four level serial SC under eight different kinds of information sharing cases, with backorder and lost sales situations. They have highlighted that the entire performance can be improved only by sharing relevant information about operating parameters of each player of SC with other players and concluded that the overall cost which is the sum of inventory cost and backorder cost/lost sales cost is used to measure the entire performance of the SC.…”
Section: Introductionmentioning
confidence: 99%
“…Further, they examined the effects of serially correlated demands on probabilistic lost-sale inventory model. Further, Ambilikumar et al (2016) have analysed the performance of a four level serial SC under eight different kinds of information sharing cases, with backorder and lost sales situations. They have highlighted that the entire performance can be improved only by sharing relevant information about operating parameters of each player of SC with other players and concluded that the overall cost which is the sum of inventory cost and backorder cost/lost sales cost is used to measure the entire performance of the SC.…”
Section: Introductionmentioning
confidence: 99%